KEDUDUKAN HUKUM PERBANKAN DALAM SISTEM OPERASIONAL BANK KONVENSIONAL - Fajar Galih Mangku Samudra; Naufal Firdaus (JURNAL ILMIAH NUSANTARA, 2024)
Banking plays a vital role in a country's economy as a financial intermediation institution that collects and distributes funds to the public. In their operations, conventional banks are required to comply with various regulations set by law and related authorities to maintain financial system stability and customer protection. Based on democratic and prudential economic principles, conventional banks aim to improve community welfare and support national development. However, the challenges faced, especially in credit-based financing models, require banks to focus more on customer success. Strict regulations aim to minimize risks in banking operations and maintain bank liquidity and solvency. In this context, the legal position of banking not only functions as a basis for legality, but also reflects social responsibility which is important for the sustainability of conventional bank operations, as well as strengthening customer trust amidst increasingly fierce competition.